Anti Urolithiatic and anti hyperlipidemic activity of Coleus aromaticus An explanation of the underlying mechanisms - Venkatesh G,; Baburao K,; Rajesh babu M,; Dhanalakshmi S,; Indira priya darshini G, (International Journal of Phytomedicine, 2010)
Leaves paste of Coleus aromaticus is used as a traditional remedy for urolithiasis in India. In the present study, the anti urolithiatic activity of Coleus aromaticus was investigated in ethylene glycol induced urolithiatic rats. There was a significant increase in the levels of calcium oxalate crystals in the kidneys as well as lipid levels in the blood serum. Treatment with hydro alcoholic extract of C.aromaticus leaves (CALHAE) significantly reduced cholesterol levels at 300 and 600 mg/kg, and triglyceride levels at 600 mg/kg in urolithiatic rats. Histopathalogical reports confirmed that chronic administration of CALHAE (300 and 600 mg/kg) diminished number of calcium oxalate crystals in kidneys. CALHAE has shown reduction in thiobarbituric acid reactive substances (TBARS) in urolithiatic rats. Moreover, CALHAE showed potent in vitro antioxidant activity in DMPD, ABTS radicals (MnO2 method). Results from these studies support the safe and effective use of C.aromaticus leaves for urolithiasis treatment.